2006
DOI: 10.2337/diabetes.55.03.06.db05-0839
|View full text |Cite
|
Sign up to set email alerts
|

The Mesenchyme Controls the Timing of Pancreatic β-Cell Differentiation

Abstract: The importance of mesenchymal-epithelial interactions in the proliferation of pancreatic progenitor cells is well established. Here, we provide evidence that the mesenchyme also controls the timing of ␤-cell differentiation. When rat embryonic pancreatic epithelium was cultured without mesenchyme, we found first rapid induction in epithelial progenitor cells of the transcription factor neurogenin3 (Ngn3), a master gene controlling endocrine cell-fate decisions in progenitor cells; then ␤-cell differentiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 38 publications
(38 reference statements)
6
67
1
1
Order By: Relevance
“…Such a point fits well with recent data where it was shown that knock-down of VEGF signaling in the embryonic pancreas does not seem to perturb the development of NGN3-positive endocrine progenitors but completely represses their differentiation into beta cells. 6 It is also supported by recent data indicating that while the expression of Ngn3 can be turned on in the embryonic pancreas using ␥-secretase inhibitors, insulin-positive cells did not develop under such conditions (30). Thus, Ngn3 induction is necessary but not sufficient for beta cells differentiation and the cellular context and additional signals seem necessary to allow NGN3-positive cells to develop into beta cells.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Such a point fits well with recent data where it was shown that knock-down of VEGF signaling in the embryonic pancreas does not seem to perturb the development of NGN3-positive endocrine progenitors but completely represses their differentiation into beta cells. 6 It is also supported by recent data indicating that while the expression of Ngn3 can be turned on in the embryonic pancreas using ␥-secretase inhibitors, insulin-positive cells did not develop under such conditions (30). Thus, Ngn3 induction is necessary but not sufficient for beta cells differentiation and the cellular context and additional signals seem necessary to allow NGN3-positive cells to develop into beta cells.…”
Section: Discussionsupporting
confidence: 69%
“…Plasmids were linearized and used as templates for synthesizing sense or antisense riboprobes using T7 or SP6 RNA polymerase (Roche Diagnostics, Meylan, France), in the presence of digoxygenin-UTP (Roche Diagnostics). In situ hybridization was done as described previously (30), and colorimetric revelation was performed with 5-bromo-4-chloro-3-indolyl phosphate (Promega, Charbonnière, France) and nitro blue tetrazolium (Roche Diagnostics) to obtain a blue precipitate. Photographs were digitized using a Hamamatsu (Middlesex, NJ) C5810 cooled 3CCD camera.…”
Section: Methodsmentioning
confidence: 99%
“…In earlier work, we showed that ␤-cells developed from embryonic pancreatic epithelium cultured in collagen gel without mesenchyme (20), whereas ␤-cells developed poorly when cultured with mesenchyme (21). This inhibitory effect of mesenchyme was due to delayed Ngn3 induction and required a functional Notch pathway (24). A working hypothesis was that hypoxia occurred in collagen gel, activating the Notch pathway and inhibiting endocrine differentiation, a mechanism recently established for other cell types (29).…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin sections (4 m thick) or cryosections (14 m thick) were prepared. A Ngn3 probe (726 bp) was used (23) and in situ hybridization was done as previously described (24). No signal was obtained when a sense riboprobe was used.…”
Section: Methodsmentioning
confidence: 99%
“…37 The authors hypothesized that this phenomenon was due to signals from remaining mesenchyme acting downstream of Ngn3 expression to prevent beta cell differentiation. We have shown previously that mesenchymal cells do not survive culture in PEGCol hydrogels, 22 both explaining this discrepancy and highlighting a benefit of culturing within a synthetic PEG hydrogel platform.…”
Section: Mason and Mahoneymentioning
confidence: 99%